CONSUMPTION PATTERNS, PRICE VOLATILITY, AND HOUSEHOLD ADAPTATION BEHAVIOR TOWARD THE RED CHILI COMMODITY IN MEDAN CITY - R. B. Moh. Ibrahim Fatoni; Rulianda Purnomo Wibowo; Dian Pebriyani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Red chili is among the most volatile horticultural commodities and a principal driver of food inflation in Medan City. This study aims to analyze household food consumption patterns, the dynamics and volatility of red chili prices, and consumer adaptation behavior in response to chili price fluctuations. A quantitative-descriptive approach was employed, drawing on a survey of 1,026 households distributed across more than thirty traditional markets, combined with daily market price data for the January 2023–September 2025 period. The data were analyzed using volatility measures (coefficient of variation) and a percentile-based threshold, price–consumption correlation, and chi-square tests. The findings reveal that food expenditure absorbs 65–75 percent of monthly household spending, while red chili is purchased by 92 percent of households on a daily-to-weekly basis, predominantly through traditional markets. The average curly red chili price reached IDR 36,890/kg with a coefficient of variation of 0.40, the highest among the commodities examined. Price and consumption are strongly and negatively correlated (r = –0.68), and the chi-square test confirms a significant relationship between chili price fluctuation and consumption reduction (χ² = 28.512; p = 0.000). Households adapt defensively by seeking cheaper markets, reducing portions, and substituting fresh chili with dried chili or bottled sauce, thereby lowering nutritional quality among low-income coastal households. The policy implications emphasize early-warning price systems, cold-chain strengthening, and supply diversification.